Ectopic pregnancy in cesarean scar: case report - Fernandez-Navarro, Manuel (2023)
Extrauterine gestation is called ectopic pregnancy, this is an obstetric emergency of the first trimester, which is having an increasing incidence. One of the locations in which these pregnancies can be generated is the scar from a previous cesarean section, which is a challenge for the treating gynecologist due to its diagnostic difficulty and therapeutic options. We report the case of a 37-year-old patient who was admitted to the emergency service with 6 weeks of amenorrhea, and with a history of 2 cesarean sections. She underwent a uterine curettage that was complicated and ended in a hysterectomy. Ectopic pregnancy in cesarean section scar is rare, however, it is important to consider this diagnostic option in pregnant women with bleeding in the first trimester with a history of cesarean section to be able to look for ultrasound signs in the evaluation.